Strategic Reasoning that promotes persistent behavior: an experimental approach - Torres-Carballo, Federico (2014)
This research aims to apply experimental techniques used to study the strategic behavior in games of Hide and Seek, as a framework for representing business situations more realistic and elaborate. To promote strategic thinking and persistence, repeated matching games between strangers are applied, and one with fixed an allocation (down payment decreases each round) with the possibility of abandonment in any round and keeping the rest of the initial allocation. In fact, the strategic reasoning is the diversion of random choices along of repetition and dropout rates of gambling, loss aversion and cultural differences that seem to frame various strategic behaviors.